THE EFFECT OF MEMRISE APPLICATION TO ENHANCE SPEAKING SKILL (A QUASI-EXPERIMENTAL AT THE ELEVENT GRADE STUDENTS SENIOR HIGH SCHOOL 03 IN BENGKULU CITY) - Indah Setyani; Riswanto; Pebri Prandika Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to investigate the effect of the Memrise application on the speaking skills of eleventh-grade students at SMAN 03 Kota Bengkulu. The study employed a quantitative approach using a quasi-experimental design with a pre-test–post-test control group design. The sample consisted of 77 eleventh-grade students, including 38 students in the experimental class and 39 students in the control class. The experimental class was taught using the Memrise application, while the control class received conventional instruction. The research instrument was a speaking test administered as both a pre-test and a post-test. Students' speaking performances were assessed by two raters using the same scoring rubric. The collected data were analyzed using validity and reliability tests, normality and homogeneity tests, the Independent Samples t-Test, and the F-Test using SPSS. The findings indicated that the data from both groups were normally distributed and homogeneous. The Independent Samples t-Test showed a significance value (Sig. 2-tailed) of 0.010, which was lower than the significance level of 0.05, indicating a statistically significant difference between the post-test scores of the experimental and control groups. Furthermore, the F-Test yielded a significance value of 0.010 with an F-value of 6.973, confirming that the Memrise application had a significant positive effect on students' speaking skills. The Partial Eta Squared value of 0.085 indicated that the treatment explained 8.5% of the variance in students' speaking achievement. Therefore, the Memrise application can be considered an effective learning medium for improving students' English-speaking skills.